Genomic landscape of acquired resistance to third‐generation EGFR tyrosine kinase inhibitors in EGFR T790M‐mutant non–small cell lung cancer. Issue 11 (10th March 2020) - Lee, Jiyun; Kim, Hong Sook; Lee, Boram; Kim, Hee Kyung; Sun, Jong‐Mu; Ahn, Jin Seok; Ahn, Myung‐Ju; Park, Keunchil; Lee, Se‐Hoon
Abstract : Background: EGFR tyrosine kinase inhibitors (TKIs) have shifted the treatment paradigm in advanced EGFR ‐mutant non–small cell lung cancer (NSCLC). However, patients who are treated with TKIs inevitably develop acquired resistance by mechanisms that are not fully understood. The purpose of this study was to investigate the mechanism of acquired resistance after treatment with third‐generation EGFR TKIs. Methods: Advanced EGFR ‐mutant NSCLC patients treated with olmutinib or osimertinib who underwent a rebiopsy before treatment or after progression were analyzed retrospectively. Targeted sequencing was performed on 113 specimens (77 pretreatment and 36 posttreatment, including 15 paired samples) obtained via tissue biopsy. Results: A total of 98 patients were included, 53 (54%) of whom were treated with osimertinib and 45 (46%) of whom were treated with olmutinib. Of the 36 patients with posttreatment biopsies, EGFR ‐dependent mechanisms, including C797S and L718Q mutations, were observed in 10 (28%) patients: 29% (5/17) in the osimertinib group and 26% (5/19) in the olmutinib group. EGFR ‐independent mechanisms were detected in 21 patients (21/36, 58%): 65% (11/17) in the osimertinib group and 53% (10/19) in the olmutinib group. The disappearance of EGFR T790M was detected in 14 patients (39%); of these patients, 59% (10/17) were treated with osimertinib and 21% (4/19) were treated with olmutinib. Patients who lost the T790M mutation were more inclined to show EGFR ‐independent pathways as a secondary resistance mechanism. Conclusion: Resistance acquired after third‐generation EGFR TKIs is associated with diverse pathways; however, treatment with osimertinib is primarily associated with a loss of EGFR T790M and the subsequent emergence of EGFR ‐independent resistance mechanisms. Abstract : Resistance acquired after treatment with third‐generation EGFR tyrosine kinase inhibitors is associated with diverse pathways and is currently not understood. The results of the present study reveal that treatment with osimertinib is primarily associated with a loss of EGFR T790M and the subsequent emergence of EGFR ‐independent resistance mechanisms.